Modified Short Beam Shear Test for Measurement of Interlaminar Shear Strength of Composites - Abali, F.; Pora, A.; Shivakumar, K.
A modified short beam shear test was proposed to measure interlaminar shear strength (ILSS)of fiber reinforced carbon-carbon composites (CCC). The direct loading in the short beam shear (SBS)test is replaced by an indirect loading through a rubber pad and an aluminum seat. This loading reduced flexure stresses to less than one fourth of the SBS test and eliminated transverse shear stress concentration under the load point. Both beam and contact finite element analyses were conducted to validate the proposed method. The finite element analysis showed that the ILSS calculated from beam equation overestimates the strength by 5 per cent for shear flexible composites. This reduction was found to be the same for both polymeric and carbon matrix composites. The test data confirmed the interlaminar shear failure and very low data scatter in measured trength. The measured ILSS of T300 CCC was 2.68 ksi and it is one of the highest values reported in literature.
Keywords: COMPOSITE MATERIAL; CARBON-CARBON COMPOSITES; INTERLAMINAR SHEAR STRENGTH; MODIFIED SHORT BEAM SHEAR TEST